Acousto-optic properties of piezoelectric interfacial waves - W. LAPRUS (Archives of Acoustics)
An analysis is given of acousto-optic coupling associated with piezoelectric interfacial waves for a great number of crystal cuts. Results of numerical calculations are presented of appropriate coupling coefficients in relation to wave parameters for lithium niobate and quartz. It is found that, for some cuts, the coefficients are quite large (over 4% for lithium niobate). It is also found that high acousto-optic coupling is usually accompanied by high piezoelectric coupling.